Progressive community organizing : transformative practice in a globalizing world - Pyles, Loretta (New York, NY : Routledge, 2021)
"Now in its third edition, Progressive Community Organizing: Transformative Practice in a Globalizing World introduces readers to the rich practice of progressive community organizing for social change while also providing concrete tools geared toward practitioner skill-building. Drawing from social movement scholarship and social theory, this book articulates a transformative approach to organizing that embraces emergent strategies and healing justice. It emphasizes framing processes and the power of stories using story-based strategy and digital activism. The book espouses intersectional organizing, addressing topics such as identity politics, microagressions, internalized oppression, and horizontal hostility with attention to re-centering and allyship as a growth-oriented journey of solidarity and liberation. Readers will engage with case studies focused on issues such as poverty, racial justice, immigration, housing, health and mental health, and climate crisis. This new edition includes: Expanded content on transformative change approaches including healing justice, new content on the role of digital technology and social media in organizing, case studies of the Poor People's Campaign and Extinction Rebellion, emphasis on the power of stories and story-based strategy for organizing and issue framing, transformative organizations with attention to feminist and decolonized organizational structures and cultures, expanded chapters on strategies and tactics focusing on power analysis and a range of tactics from direct action to resilience-based organizing The book will be of interest to students and practitioners who want to become more skilled in structural analysis, praxis, and self-reflexivity through critical and transformative engagement with historical and current social problems, social movements, and social welfare"--
The bedrock of community organizing -- Transformative practice -- Theories and praxis -- Learning from social movements -- Community organizing frameworks -- Organizing people -- Tranformative organizations -- Communication for social change: issue framing, storytelling, and social media -- Strategy and power -- Tactics for change -- Intersectionality, solidarity, and liberation -- Religious and spiritual aspects of organizing -- Global justice amidst climate crisis.
OCLC-licensed vendor bibliographic record.
Keywords: Community organization; Social action; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health